Free revealing in open innovation: a comparison of different models and their benefits for companies. (1st January 2011) - Schweisfurth, Tim; Raasch, Christina; Herstatt, Cornelius
In open innovation processes, free-revealing of information has proliferated in the wake of distributed electronic communication systems. Many scholars have coined a multitude of concepts to explain this free-revealing phenomenon and to develop models of organising innovation based on it. These models are partly overlapping, partly exclusive, and partly encompassing. In an extensive literature review, we identify five such concepts and research streams: collective invention, user innovation networks, commons-based peer production, crowdsourcing and open-source innovation. We compare and contrast these models along several dimensions. We present an integrative perspective on the five models and derive implications for research and practice.